Studies on the mechanism of the formation of yield differences in indica–japonica hybrid rice - Kailiang Mi; Yiyin Lu; Muyan Zhang; Fangfu Xu; Yanju Yang; Haipeng Zhang; Hongcheng Zhang (BMC Plant Biology)
Abstract Population characteristics serve as crucial determinants of rice yield. Investigating the population characteristics of indica–japonica hybrid rice across different yield levels can offer a solid theoretical foundation and robust scientific evidence for enhancing high-yield cultivation and breeding efficiency. This study conducted a two-year field experiment on four indica–japonica hybrid rice varieties with three planting densities. The results show that the super-high-yielding of indica–japonica hybrid rice is mainly attributed to its higher total spikelets and dry matter accumulation. Compared to high-yielding indica–japonica hybrid rice, the total spikelets increased by 12.66%–24.49%, and dry matter accumulation increased by 10.82%–19.42%. In addition, the super-high-yielding indica–japonica hybrid rice also exhibited advantages in harvest index, percentage of productive tiller, grain density, and SPAD value after heading. As the planting density of indica–japonica hybrid rice increases, its yield also increases. For the four varieties, the yield increases by 3.21%–5.95%, 1.87%–6.77%, 2.75%–10.57%, and 2.00%–4.45%, respectively. An analysis of the yield components reveals that the primary driver of the yield increase is the rise in total spikelets, which is attributed to a greater number of effective panicles. For the four rice varieties, the total spikelets respectively increased by 5.15%–10.64%, 3.34%–12.88%, 5.79%–14.33%, and 3.46%–11.56%. However, the higher initial plant population density led to vigorous growth of nonproductive tillers. This reduced the percentage of productive tillers and accelerated the leaf area reduction rate. This resulted in lower SPAD values, restricted plant growth manifested as decreased plant height, and reduced length, width, and angles of the top three leaves. Concurrently, panicle development was constrained, exhibiting shorter panicle length, fewer panicle branches, and decreased seed-setting rate, 1000-grain weight, and spikelets per panicle. In summary, in agricultural production, selecting indica–japonica hybrid rice varieties with super-high-yielding potential and increasing their planting density is of great significance for ensuring food security.